Research on axial dynamic process of power transformer windings under short-circuit shock - Ou, Yangli; Yan, Yunfei; Hou, Xiaolin; Yang, Kuidong; Zhang, Wei; Zhong, Chaoyang; Wang, Xiaohui; Yu, Zhanyang; Ma, Mingze (Frontiers in Energy Research, 2025)
As the core component of transformer, when the transformer is hit under short-circuit condition, the huge electromagnetic force will seriously aggravate the axial vibration of winding and even cause the damage of winding structure. In this paper, the electromagnetic load of transformer winding under short-circuit impact is solved, and based on the “spring-mass” model, the time-varying process of vibration displacement in the initial stage of short-circuit consists of 50 Hz and 100 Hz components. The axial dynamic process of inner winding is calculated by the simulation analysis method for transient structural field. It is found that the winding with the largest axial vibration displacement is not the winding with the largest axial electromagnetic force, and the axial vibration distribution of the winding is M-shaped. Based on the calculation model of one winding span, the axial vibration of the winding under non-uniform load is presented, which has an obvious stepped distribution at the interval of the spacers. And the vibration of the wingding between two spacers is larger than that at the end compression position. Finally, through the winding vibration test of the model transformer, the accuracy of the winding vibration model and the winding vibration distribution law are verified.